22.1: Invited Paper: Low‐Voltage Polymer‐Stabilized Blue‐Phase Liquid Crystals. Issue 1 (1st July 2013) - Haseba, Yasuhiro; Yamamoto, Shin‐ichi; Sago, Kohki; Takata, Akihiro; Tobata, Hitoshi
Abstract: The operating voltage of PS‐BPLCs could be reduced by using host nematic liquid crystals with extremely large ΔnXΔε One of the PS‐BPLCs showed 23V of Vmax and 800 of contrast ratio using IPS electrode with 10μm of spaces, which should be driven by normal driver if electrode design is optimized On the other hands, such PS‐BPLCs with large Δε also took a long charging time to be charged enough as a side effect. This charging problem has to be solved by improvement of materials, devices and driving method so that low voltage PS‐BPLCs will be widely used